سمات التفسير اللغوي في تفسير الطبريSimāt al-Tafsīr al-Laghawi in Tafsīir al-Tabarī (Al-Qamar, 2020)
This research shows up theone dide of Imam Abu Jaafar al - Tabari's interest in linguistic interpretation and how he gives it  a large space in the field of interpretation. It also shows clearly his interest in the meanings of the vocabulary and the state of the structure and his application of etymology to know the origin of the Arabic use of the word, so that hardly a Quranic word passes through it without being exposed to its linguistic statement. His linguistic interpretation is also distinguished by several characteristics, including: His focus is on highlighting the original meaning of the term, as he often reveals the word when explaining it and says: Its origin is such - and most of its reliance in this section is on the early imams who knew the language.
Keywords: Smaat al-Tafsir; al-Laghawi; al-Tabari